Spontaneous Vesicouterine Fistula: A Case Report - Aykut Başer; Ali Ersin Zümrütbaş; Yusuf Özlülerden; Hülya Yılmaz Başer; Cihan Toktaş; Zafer Aybek (Journal of Urological Surgery, 2017)
Vesicouterine fistulae (VUFs) are the least common type of urogenital fistulae and they are usually associated with lower segment caesarean section. The classic triad of VUF has been defined as urinary incontinence, amenorrhea, and cyclic hematuria. In the literature, spontaneous VUF without a history of previous surgery or radiotherapy has not been reported before. In this report, we present a female patient who presented with continuous urinary incontinence and was diagnosed with VUF. The patient was managed with cystectomy and hysterectomy and ileal conduit diversion. To our knowledge, this is the only reported case of spontaneous VUF.